Ergotismo cronico en añojos - Muñoz, M.C.=700 1 Merino, N.; Marrero, E.; Palenzuela, I.
(Es, En)
Ilus., 10 ref.
Keywords: GANADO BOVINO; ENVENENAMIENTO; ERGOTINAS; INGESTION; PIENSOS; CONTAMINACION; ALCALOIDES; CUBA